(untitled) (Altre Modernità, 2021)
The central subject of Marlen Haushofer’s famous novel The Wall is the reflection of alienation as “relationship of relationshiplessness” (Rahel Jaeggi). It reflects on this by resorting to a metaphor for alienation that has become topical: the glass wall. The novel’s innovative literary effort is that it takes this metaphor literally in the form of a wall that suddenly appears and extends endlessly into the world. This literalization of the metaphor, however, does not result in overcoming alienation in the sense of liberating the nameless main character. Rather, it is part of a genuinely creative procedure – a procedure that Deleuze and Guattari, following Franz Kafka, call “way out”. And a procedure for which the protagonist must pay the price of an inescapable ambivalence.